2005
DOI: 10.1073/pnas.0500489102
|View full text |Cite
|
Sign up to set email alerts
|

Reversible single-molecule photoswitching in the GFP-like fluorescent protein Dronpa

Abstract: Reversible photoswitching of individual molecules has been demonstrated for a number of mutants of the green fluorescent protein (GFP). To date, however, a limited number of switching events with slow response to light have been achieved at the single-molecule level. Here, we report reversible photoswitching characteristics observed in individual molecules of Dronpa, a mutant of a GFP-like fluorescent protein that was cloned from a coral Pectiniidae. Ensemble spectroscopy shows that intense irradiation at 488 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
462
6
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(501 citation statements)
references
References 26 publications
31
462
6
2
Order By: Relevance
“…2). The 9-ps component is assigned to the decay of the singlet excited state of the neutral trans chromophore, in agreement with previous fluorescence measurements 9 . Habuchi et al 9 reported a 14-ps time constant for fluorescence measurements of the off state of Dronpa in 1 H 2 O at pH 7.4, with excitation at 390 nm and detection at 440 nm.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2). The 9-ps component is assigned to the decay of the singlet excited state of the neutral trans chromophore, in agreement with previous fluorescence measurements 9 . Habuchi et al 9 reported a 14-ps time constant for fluorescence measurements of the off state of Dronpa in 1 H 2 O at pH 7.4, with excitation at 390 nm and detection at 440 nm.…”
Section: Resultssupporting
confidence: 91%
“…Spectroscopic contrast is primarily developed via protonation/ deprotonation of the phenolic oxygen such as that in GFP. This has been proposed to develop via excited-state proton transfer (ESPT) [9][10][11] (Supplementary Note 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Alexa 647, Dronpa, Dreinklang and rsEGFP) 3,[18][19][20] and (ii) irreversibly photoactivatable and photoconvertible (e.g. PA-GFP, PA-mCherry, mEos2, mEos3.1, mEos3.2, Dendra2, mClavGR2 and mMaple) [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%